2012
DOI: 10.1007/s00221-012-3021-z
|View full text |Cite
|
Sign up to set email alerts
|

Tool use without a tool: kinematic characteristics of pantomiming as compared to actual use and the effect of brain damage

Abstract: Movement goals and task mechanics differ substantially between actual tool use and corresponding pantomimes. In addition, apraxia seems to be more severe during pantomime than during actual tool use. Comparisons of these two modes of action execution using quantitative methods of movement analyses are rare. In the present study, repetitive scooping movements with a ladle from a bowl into a plate were recorded and movement kinematics was analyzed. Brain-damaged patients using their ipsilesional hand and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…For example, when healthy subjects pantomime scooping soup from one pot to another with a ladle, they roll their hand above the pots even more than when they perform the same activity with real ladles and real soup. Subjects with aphasia and apraxia, comparable to the participants of this study, frequently omit the additional movement (Hermsdörfer, Li, Randerath, Goldenberg, & Johannsen, 2012). Their pantomimes thus become more realistic but less comprehensible than those of healthy subjects.…”
Section: Predictors Of Comprehensibility Of Gesturesmentioning
confidence: 90%
“…For example, when healthy subjects pantomime scooping soup from one pot to another with a ladle, they roll their hand above the pots even more than when they perform the same activity with real ladles and real soup. Subjects with aphasia and apraxia, comparable to the participants of this study, frequently omit the additional movement (Hermsdörfer, Li, Randerath, Goldenberg, & Johannsen, 2012). Their pantomimes thus become more realistic but less comprehensible than those of healthy subjects.…”
Section: Predictors Of Comprehensibility Of Gesturesmentioning
confidence: 90%
“…To date, most studies in normal aging explored kinematic changes in reaching and grasping meaningless objects, such as geometrical shapes, while the kinematics of tool use have been assessed mainly in adults with apraxia (Hermsdörfer, Hentze, & Goldenberg, 2006;Hermsdörfer, Li, Randerath, Goldenberg, & Johannsen, 2012;Laimgruber, Goldenberg, & Hermsdörfer, 2005;Poizner, Mack, Verfaellie, Rothi, & Heilman, 1990;Poizner et al, 1995;Sunderland, Wilkins, & Dineen, 2011). In the studies on apraxia, the presence or absence of a tool in the patient's hand during the actual execution of the movement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this aspect has not yet been specifically explored in normal aging, even though it does appear relevant given that elderly adults seem to benefit from the ecological value of the tasks (Bennett & Castiello, 1994;Carnahan, Vandervoort & Swanson (1998) Varadhan et al, 2012). For instance, grasping a common tool with the purpose of using it may be more natural and automatic than grasping to move an object, since the affordances of the object may automatically evoke the motor program specifically related to the use of the object (Hermsdörfer et al, 2012;Tucker & Ellis, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a lot of evidence from clinical studies indicates a major role of the left hemisphere of the brain in accessing and processing the knowledge of tools and tool use. For instance, Hermsdorfer, Li, Randerath, Goldenberg & Johanssen (2012) found that patients with left hemisphere stroke exhibited reduced hand rotation at the bowl and the plate in pantomiming as well as actual use. Randerath, Goldenberg, Spijkers, Li & Hermsdorfer (2010) found a large area of lesion overlap in the left supramarginal gyrus for patients with impaired tool use whereas lesion overlap in the left inferior frontal gyrus and left angular gyrus for patients who were impaired in tool grasping.…”
mentioning
confidence: 99%